The influence of Kangaroo Mother Care (KMQ) on self-esteem in mother with 1 preterm infants - Rewina Intan A, - (Ikatan Dokter Anak Indonesia - IDAI, 2016)
Background:Kangaroo Mother Care (KMC)is a caring approach for preterm infants, not just prevent hypothermia but also on maternal selfesteem. Self-esteem is an essential component of mothering with holding will make a woman's sense about herself as a mother is reflected in the mother-infant relationship. Objective: To identify the influence of KMC on self-esteem Methods: An experimental study to examine self-esteem of mother who had preterm neonate in NICU Soetomo Hospital on April 2016 were analyzed by Roosenberg Self-Esteem Scale (RSES), with total score 30 (low:<15, high:>25). Self-esteem scale compared between KMC and non KMCgroup. KMC given one time daily for 2 hours during at least 3 days mother had assessed by RSES.Statistical analysis used independent T-Test and Pearson correlation test. Results: This studied was ducted with KMC group of 22 (45%)infants, and non-KMC group of27 (55%) infants. The mean of mother age in KMC group (26.4(SD 5.8) vs. 27.l (SD 5.8} years old)and gestational age (33.2(SD 2.2) vs 31.8(SD 2.5) weeks) was not significantly different in the both group (P=0.7;P=0.54). There was no significant effect of mother age (r=O. 15;P=0.29) and gestational age (r-0.07;P=0.61) with the values of RSES. The mean of RSES of the K.MC group20.5(SD 4.8) with range score 12-28. In non KMC group, the mean score was 11.96 (SD 4,39) with range score 5-23.The score of the K.MC group were significant higher than non-KMC group(P=0.00). Conclusion: Mother in KMC is a higher RSESsthan mother in non-KMC group.